A study on securing model usefulness through geographical scalability testing of winter weather model developed with big traffic data. Issue 6 (18th August 2022) - Roh, Hyuk-Jae
ABSTRACT: Few previous studies have conducted spatial transferability of the winter traffic models' parameters between homogeneous and heterogeneous road segments during the winter season. This research pursues the purpose of using traffic data collected from five WIM sites in Alberta, Canada. Winter traffic models are developed for one weigh-in-motion site, and the other four sites, each representing different traffic characteristics, are used to verify the spatial transferability of the developed model. This research aggregated the traffic data into three vehicle types to develop winter traffic models by associating traffic data with climatic information. This research has demonstrated that the winter traffic models developed for the roads serving one specific travel population can be transferred with high accuracy to homogeneous and heterogeneous road segments.